Workspace and Payload-Capacity of a New Reconfigurable Delta Parallel Robot. (21st January 2013) - Maya, Mauro; Castillo, Eduardo; Lomelí, Alberto; González-Galván, Emilio; Cárdenas, Antonio
In this paper the workspace and payload capacity of a new design of reconfigurable Delta-type parallel robot is analysed. The reconfiguration is achieved by adjusting the length of the kinematic chains of a given robot link simultaneously and symmetrically during the operation of the robot. This would produce a dynamic workspace in shape and volume. A numerical analysis of the variation of shape and volume of the workspace and payload capacity of the robot is presented. Based both on the results of this analysis and on practical requirements, a proposal for the design of a reconfiguring mechanism is presented.